2006
DOI: 10.4102/sajpsychiatry.v12i2.62
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for psychiatric morbidity among tertiary hospital consultants in Nigeria

Abstract: <p><strong>Objective.</strong> To determine the prevalence of psychiatric morbidity among consultants in a tertiary health care institution in Ilorin, Nigeria, and the sociodemographic and work characteristics that may be associated with poor mental health.</p><p><strong>Method.</strong> This was a cross-sectional study involving use of the 30-item general health questionnaire (GHQ-30) and a questionnaire on sociodemographic/work-related factors. <strong></str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…This result is similar to some earlier international studies. 27,28 Similar observations have been fielded locally, for instance, Yusuf et al, 12 reported a prevalence of psychiatric morbidity in about one in four (25.7%) residents in Ilorin, in Northern Nigeria; likewise Ogunniyi [Ogunniyi SO (2005) Psychiatric Morbidity among resident doctors in a Nigerian Teaching Hospital. A dissertation submitted for the award of fellowship by the West African College of Physician] reported a closely similar point prevalence of psychiatric morbidity (27.1%) among the resident doctors in similar context.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This result is similar to some earlier international studies. 27,28 Similar observations have been fielded locally, for instance, Yusuf et al, 12 reported a prevalence of psychiatric morbidity in about one in four (25.7%) residents in Ilorin, in Northern Nigeria; likewise Ogunniyi [Ogunniyi SO (2005) Psychiatric Morbidity among resident doctors in a Nigerian Teaching Hospital. A dissertation submitted for the award of fellowship by the West African College of Physician] reported a closely similar point prevalence of psychiatric morbidity (27.1%) among the resident doctors in similar context.…”
Section: Discussionsupporting
confidence: 58%
“…Such factors include high patient work load, poor work environment, distant accommodation, lack of recreational services, indebtedness, length of time spent in training, lack of social support, problems of relocation, difficult patients, and gender related issues among others. [8][9][10][11][12][13] The impact of unattended mental health disorders like anxiety disorders in the setting of work place is significant; frequently described in terms of direct (associated with the cost of treatment) and indirect (that is related to reduction in productivity due to the illness) costs. For instance, previous estimate in the United States reported about 46.6 billion dollars as the annual economic costs associated with anxiety disorders, and this constitutes 13.1% of the expenditure for mental illness.…”
mentioning
confidence: 99%
“…Distribution/retrieval was according to their serial/matriculation numbers, to enable appropriate matching at the subsequent surveys especially, the 1st year students who were planned for a longitudinal survey. Using a cut-off point of 3 in line with previous studies among students and occupational groups in this environment [24][25][26][27] , students who scored ≥3 on General Health Questionnaire-12(ghq-12) were regarded as having psychiatric morbidity (i.e., 'ghq-12 cases') [24][25][26][27] , and those who scored <3, were regarded as having no morbidity (i.e., 'ghq-12 'non-cases').…”
Section: Methodsmentioning
confidence: 99%
“…The GHQ scoring method (0-0-1-1) was adopted, and a cut-off point of 3 was used in accordance with previous studies (and is noted as "psychiatric morbidity" in the Results section). 2,3,[24][25][26][27][29][30][31][32][33] Sources of stress questionnaire The 28-item source of stress questionnaire previously used by Sreeramareddy et al 17 was adapted with subtle adjustments to the contents (e.g., substituting 'cafeteria' for 'hostel' in item 1, and 'clinical rotation' for 'practical' in item 19). The questionnaires were pre-tested among 20 first year Laboratory Medical students for face and content validities.…”
Section: General Health Questionnaire-12 (Ghq-12)mentioning
confidence: 99%
See 1 more Smart Citation